Historians across borders: writing American history in a global age - Barreyre, Nicolas; Heale, Michael; Tuck, Stephen G. N.; Vidal, Cécile (University of California Press, 2014)
"In this stimulating and highly original study of the writing of American history, twenty-four scholars from eleven European countries explore the impact of writing history from abroad. Six distinguished scholars from around the world add their commentaries. Arguing that historical writing is conditioned, crucially, by the place from which it is written, this volume identifies the formative impact of a wide variety of institutional and cultural factors that are commonly overlooked. Examining how American history is written from Europe, the contributors shed light on how history is written in the United States, and, indeed, on the way history is written anywhere. The innovative perspectives included in Historians across Borders are designed to reinvigorate American historiography as the rise of global and transnational history is creating a critical need to understand the impact of place on the writing and teaching of history. This book is designed for students in historiography, global and transnational history, and related courses in the United States and abroad, for US historians, and for anyone interested in how historians work"--
Literaturverzeichnis: Seite 291-294
Keywords: United States -- Historiography; United States -- History -- Study and teaching -- Europe; Aufsatzsammlung; Geschichtsschreibung; USA; Europa